PREDIKSI DEGRADASI THROUGHPUT JARINGAN 4G LTE PADA DRONE KECEPATAN TINGGI, MENGGUNAKAN MODEL GARCIA-ALFREDSSON-BRUNSTROM-BECKMAN - Agung Wirjawan; Rahmad Hidayat (Jurnal Online Sekolah Tinggi Teknologi Mandala, 2022)
4G LTE network is designed for stationary User Equipment (UE), or user moving at low speed. High speed IOT drones will degrade the performance of the network, especially throughput, when the drone is functioningas an Aerial UE (AUE). To find out the throughput degradation, and what the degraded throughput, predictions are made using the model developed by Garcia-Alfredsson-Brunstrom-Beckman. SINR and throughput when the drone is in stationary state are cited from the results of field measurements on Indosat's 4G LTE network in the Kupang Airport area. The data is then processed using Webplotdigitizer and Excel applications to predict throughput at a drone speed of 161 km/hour. The prediction results show that download throughput is about 5.19 – 23.11 Mbps, upload throughput is about 18.53 – 27.64 Mbps, and throughput degradation is between 0.73 to -0.68 Mbps depending on the SINR level, the higher the SINR the lower the degradation. From the results of these predictions, it can be seen that Indosat's network in the Kupang Airport area is sufficient to support IOT drone operations at speeds of up to 161 km/hour, because even though it is degraded, the throughput is still sufficient to transmit control and video signals between drones and controllers on the ground via the network, i.e. 250 Kbps for download and 8.25 Mbps for upload.